Embung Development for Palm Oil Industry Water Supply Based on Soil Water Assessment Tools - Muzhaffar Harits; Asep Sapei; Nora Herdiana Pandjaitan (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
The water supply at the IPB Education and Research Garden Jonggolis generally sourced from rainfall. This can lead to water shortage during certain periods, so building a water storage structure such as a small reservoir (embung) is necessary. The embung can provide a more stable water supply by storing rainwater and river inflow. This research aims to design an embung at the IPB Education and Research Garden Jonggol, and to analyze the water balance of the planned embung. This study presents the application of SWAT-based dependable discharge analysis for small-scale industrial reservoirs in tropical regions. The findings support sustainable water management and enhance enhance agro-industrial resilience, particularly in regions dependent on rainfall. The planned embung is designed for the palm oil processing plant with a total water requirement of 8,786 m3 in the dry season. Dependable discharge analysis is conducted using Soil Water Assessment Tool (SWAT), while flood discharge analysis uses the rational method. Embung capacity design is based on water availability, water requirement, sediment volume, and total evaporation. The planned embung will be located at coordinates 107° 2' 10.53